A dimmable Light-emitting diode (LED) driver with cascaded mag-amp postregulators for multistring applications - Chen,W; Hui,SYR (IECON Proceedings Industrial Electronics Conference, 2010)
A dimmable LED driver with cascaded magnetic amplifiers is proposed for multistring applications. A master power converter is used to provide the major part of the voltage for a plurality of slave converter modules with magnetic amplifier control. The magnetic amplifiers are used to regulate only the varying part of the LED string voltage and therefore greatly reduce the power losses in parallel converter modules. Good current balance among the parallel LED strings and a high energy efficiency in the range of 86-88% has been achieved for a 21W practical prototype formed with 3 parallel strings. © 2010 IEEE.